CFD analysis of rotating diffuser in a SUV vehicle for improving thermal comfort. (2022) - Karthick, L.; Prabhu, D.; Rameshkumar, K.; Prabhu, T.; Jagadish, C.A.
Abstract: Nowadays, most of the cars have air conditioning as a standard feature, which improves comfort and safety. Automatic temperature control, incorporated cooling, warming, de-misting and de-frosting, air filtration, humidity management, and safety are all characteristics of modern systems. The interior cabin temperature has the greatest impact on passenger thermal comfort. Cabin temperature is to determine by the size of the cabin, the quantity and form of air vents, the overall HVAC system's mass flow rate, and the dashboard, trimmings, and seating materials. The vanes are adjusted manually to establish the airflow direction and in few, it is automatically adjusted. The round-shaped set-up in the cabin's HVAC system has a dynamic mechanism that is mean to spin at a constant speed along its axis. In this work, SUV vehicle cabin has investigated with different speed and find the suitable temperature range. It should be test using CFD software and steady state thermal analysis. According to ANSYS FLUENT, the observed cabin findings include a temperature of roughly 23 °C and an airflow velocity of 5 m/sec.